2015
DOI: 10.1007/s11105-015-0888-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Peppermint (E)-β-Farnesene Synthase Gene in Rice Has Significant Repelling Effect on Bird Cherry-Oat Aphid (Rhopalosiphum padi)

Abstract: Aphids (Aphididae) cause great damage to economically important cereal crops due to their unparalleled reproductive capacity. The sesquiterpene (E)-β-farnesene (EβF) is the alarm pheromone for many aphids, which can be applied to disperse aphids in crops. The peppermint EβF synthase gene (EβFS), which enables the production of EβF in plants to control aphids, has been used in Arabidopsis and tobacco, but has not been studied in rice or other crops yet. Here, we transformed the peppermint EβFS gene into the ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…The coupled GC–MS analysis and behavior results showed that the transgenic alfalfa emitted EβF, and repelled pea aphids under laboratory conditions. Similar results have been observed with peach aphids M. persicae to Arabidopsis and Nicotiana tabacum (tobacco), and bird cherry‐oat aphid Rhopalosiphum padi to Oryza sativa (rice) . These results suggested that EβF synthase gene can more functionally increase pea aphid aversion to transgenic alfalfa, with the targeted gene approach offering a feasible option to reduce aphid infestations in alfalfa.…”
Section: Discussionsupporting
confidence: 80%
“…The coupled GC–MS analysis and behavior results showed that the transgenic alfalfa emitted EβF, and repelled pea aphids under laboratory conditions. Similar results have been observed with peach aphids M. persicae to Arabidopsis and Nicotiana tabacum (tobacco), and bird cherry‐oat aphid Rhopalosiphum padi to Oryza sativa (rice) . These results suggested that EβF synthase gene can more functionally increase pea aphid aversion to transgenic alfalfa, with the targeted gene approach offering a feasible option to reduce aphid infestations in alfalfa.…”
Section: Discussionsupporting
confidence: 80%
“…There is a medium-sized gene family for most plant genomes with encoding terpene synthetases. It is important for studying the physiological and 4 ecological functions of the specific terpenoids by using the plants that overexpress the TPS gene [15,[23][24][25][26][27]. Over expression of the wheat FPP synthase gene (FPS) in Arabidopsis could repel the Myzus persicae Sulzer [26].…”
Section: Introductionmentioning
confidence: 99%
“…The generation of genetically modified plants with overexpressed TPS genes is useful in studying the physiological and ecological functions of specific terpenoids (Aharoni et al ; Degenhardt et al ; Brillada et al ; Gao et al ; Zhang et al ). For example, targeting of the TPS gene FaNES1 of strawberry Fragaria × ananassa, into A. thaliana mitochondria resulted in the recruitment of carnivorous predatory mites through the enhanced production of ( E )‐nerolidol and DMNT (Kappers et al ).…”
Section: Introductionmentioning
confidence: 99%